The Implementation of Enterprise Risk Management (ERM) to Improve the Accuracy of Credit Decision-Making: A Case Study of Consumer Cooperative X – Savings and Loan Unit (USP) “Gajian di Muka” Product - Luri Rahman Anharudin; Ktut Silvanita Mangani; Wilson Rajagukguk (AGUSPATI Research Institute, 2026)
This study aims to analyse credit risk in Consumer Cooperative X, specifically within the Savings and Loan Unit (USP) for the “Gajian di Muka” product, by applying Enterprise Risk Management (ERM) based on ISO 31000:2018 through a Failure Mode and Effects Analysis (FMEA) approach. The background of this study is driven by the increasing ratio of non-performing loans (NPL) exceeding the cooperative’s tolerance threshold, as well as weaknesses in credit verification and monitoring processes that affect the accuracy of credit decision-making. This research employs a descriptive qualitative method through in-depth interviews and document analysis to assess the severity, occurrence, and detection capability of credit risks. The root causes were identified using a fishbone diagram combined with the 5 Why approach, and subsequently analysed using FMEA to obtain the Risk Priority Number (RPN). The findings indicate that several credit risks with high RPN values require priority mitigation, particularly those related to weaknesses in data verification, limited supervision, and the lack of an optimal early warning system. Following the implementation of ERM–FMEA-based mitigation strategies, credit risk can be controlled through improved operational procedures, strengthened verification systems, and the development of an early warning system. These findings demonstrate that the integration of ERM and FMEA is effective in enhancing early risk detection, reducing potential credit risk, and improving the accuracy of decision-making as well as the operational sustainability of the cooperative.